Pola Pewarisan Tradisi Lisan Kabhanti Modero pada Masyarakat Muna Di Sulawesi Tenggara - Samsul . (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2015)
This research aims at expressing about the inheriting pattern of Oral tradition of Kabhanti Modero to Munanese People in South East Sulawesi. This research was done in three districts in Muna Regency namely Duruka, Lohia, and La Salepa districts. Data source in this research are field and library data. The method used in this research is ethnographic method. With ethnographic method, local community’s knowledge about the inheriting pattern of kabhanti modero can be expressed. Data collecting were done by two ways, namely field and library data. The field research was done by some techniques, i.e. participatory observation, interview, and recording techniques. Library data were done by finding out the data or references related with the object of research. Data in this research were analyzed by using qualitative descriptive analysis. The findings showed that nowadays the inheriting pattern of kabhanti modero is still done in non formal way. Non formal inheriting is conducted through direct inheriting, internal family inheriting and in-performing inheriting. The inheriting through record industry of VCD or DVD cassettes has not been done in kabhanti modero. Formal inheriting has not been carried out up to now. The formal inheriting means making kabhanti modero to be included in local load curriculum or Cultural Art subject as the cultural heritage of Munanese people. Keywords: inheriting pattern, oral tradition, kabhanti moder